Over-professional skills «soft skills» in the process of personal self-improvement of future teachers of higher educational institutions - Shaparenko, Khrystyna; Bakumenko, Tetyana; Roganov, Maxim (My University, 2020)
The development of a teacher's personality today is becoming an important component of a holistic educational process, and its result should be a person who is a model for moral behavior and spiritual development, who is focused on the values of world and national culture, capable of creative self-realization and self-improvement in the professional and pedagogical sphere and in the world, cultural values. Therefore, we can conclude that the search for a solution to the entire complex of civilizational problems lies on the path of the spiritual revival of man and society, namely through the process of personal self-improvement.
Shaparenko Khrystyna Over-professional skills «soft skills» in the process of personal self-improvement of future teachers of higher educational institutions / Khrystyna Shaparenko, Tetyana Bakumenko, Maxim Roganov // Organizational problems of life quality management in the conditions of globalization : мonograph / editors : Marian Duczmal, Tetyana Nestorenko. – Opole : The Academy of management and administration in Opole, 2020. – C. 8‒12.
Keywords: soft skills, self-improvement, acmeology, flexible skills, creative potential, сompetence